Thank God my car is born again so Am I: naturalistic observation of religious inscriptions on vehicles in Nigeria (2008)
The study investigated the frequency of religious inscriptions, the use of religious stickers, and religious orientation amongst vehicle owners in Lagos city of Nigeria. A naturalistic observation of 430 cars, 140 commercial buses and 40 trailers was carried out at first, then a sample of 100 participants (68 males and 32 females) selected from a cross section, of private car owners, and commercial drivers in Lagos metropolis were given questionnaire to-complete. The independent variable was religion. The dependent variable was measured with Sticker use and Religious Behaviour Scale (SRBS) (X=39.90; S.D 6.09) and Religious Orientation Questionnaire (ROQ) (X = 12.58); S.D = 4.44). The results obtained revealed that four hypotheses were significant. With this, it was concluded that though there are more religious stickers than other stickers 011 cars and other vehicles in Nigeria, religious sticker use does not imply religiousity.